2021
DOI: 10.3390/su132413989
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability: A Public Policy, a Concept, or a Competence? Efforts on the Implementation of Sustainability as a Transversal Competence throughout Higher Education Programs

Abstract: The concept of sustainability emerged globally in the 1987 Brundtland Report. Initially, it comprised three dimensions: environmental, social, and economic. Over time, sustainability became a global necessity that led to the establishment in 2015 of the 17 Sustainable Development Goals (SDGs), so that sustainability became a public policy of extreme urgency. Thirty-four years later, there is an imperative need to expand the original concept not in a public policy but in a competence that graduates of higher ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
14
0
3
Order By: Relevance
“…The theoretical framework that supports the inclusion of experiences of recognition and appreciation of cultural heritage is based on the principles of education for sustainable development (ESD) of UNESCO, according to which sustainable development is an ethical challenge as well as a scientific concept (Membrillo-Hernández et al, 2021b). We based our research on the following premises: First, STEAM education (STEM + Arts) is an approach that responds to the imperative need to prepare young people to develop innovation and creativity skills to positively and productively face the global challenges of the 21 st century that are affecting the economy, the natural environment, and our diverse cultural heritage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical framework that supports the inclusion of experiences of recognition and appreciation of cultural heritage is based on the principles of education for sustainable development (ESD) of UNESCO, according to which sustainable development is an ethical challenge as well as a scientific concept (Membrillo-Hernández et al, 2021b). We based our research on the following premises: First, STEAM education (STEM + Arts) is an approach that responds to the imperative need to prepare young people to develop innovation and creativity skills to positively and productively face the global challenges of the 21 st century that are affecting the economy, the natural environment, and our diverse cultural heritage.…”
Section: Methodsmentioning
confidence: 99%
“…One proposed approach that will both seek to enrich STEM student learning while promoting the care of cultural heritage may be attained through the implementation of pedagogical strategies of a Socially-Oriented Education (SOE). Using techniques such as challenge-based learning (CBL), we may be able to guide students to gain empathy and skills towards the sustainability and cultural care required to maintain world heritage (Membrillo-Hernández et al, 2021a;Membrillo-Hernández et al, 2018;Membrillo-Hernández et al, 2021b).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability appears to be a modern concept that encompasses many ideas, but its meaning has evolved over time, with the most common connotation being something that lasts, is eternal, or that by its nature remains present, without consuming something externally harmful, and applying this to many areas of knowledge or society [32]. It is widely accepted "that sustainable development meets the needs of the present without compromising the ability of future generations to meet their own needs" [33].…”
Section: The Covid-19 Pandemic and The Development Of Electromobility...mentioning
confidence: 99%
“…Several studies and curriculum redesign initiatives have shown that sustainability is a transversal skill that must be integrated in curriculum at all levels. (Membrillo-Hernández et al, 2021) Societies in the twenty-first century face the difficult task of swiftly transforming towards sustainability while balancing the complicated trade-offs between ecological, social, and economic factors (Raworth, 2012). Deeply rooted learning processes with regard to abilities, knowledge, and values are essential to reconcile human well-being and the integrity of geo-bio-chemical processes necessary for all life on Earth (Sterling, 2016).…”
Section: Introductionmentioning
confidence: 99%